The psychosocial flags framework: overcoming obstacles to work - Burton, Kim (Henry Stewart Talks, 2015)
Back pain: symptoms of episodic patterns, Various ways of coping with back pain, The determinants of disability (psychosocial vs. injury), Psychosocial factors as obstacles to work participation, The key to help: Evidence-informed Psychosocial Flags Framework